Systematic review of patient and caregivers’ satisfaction with telehealth videoconferencing as a mode of service delivery in managing patients’ health - Orlando, Joseph F.; Beard, Matthew; Kumar, Saravana (PLOS ONE, 2019)
Telehealth is an alternative method of delivering health care to people required to travel long distances for routine health care. The aim of this systematic review was to examine whether patients and their caregivers living in rural and remote areas are satisfied with telehealth videoconferencing as a mode of service delivery in managing their health. A protocol was registered with PROSPERO international prospective register of systematic reviews (#CRD42017083597) and conducted in line with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. A systematic search of Ovid Medline, Embase, CINAHL, ProQuest Health Research Premium Collection, Joanna Briggs Institute and the Cochrane Library was conducted. Studies of people living in rural and remote areas who attended outpatient appointments for a health condition via videoconference were included if the studies measured patient and/or caregivers’ satisfaction with telehealth. Data on satisfaction was extracted and descriptively synthesised. Methodological quality of the included studies was assessed using a modified version of the McMaster Critical Review Forms for Quantitative or Qualitative Studies. Thirty-six studies of varying study design and quality met the inclusion criteria. The outcomes of satisfaction with telehealth were categorised into system experience, information sharing, consumer focus and overall satisfaction. There were high levels of satisfaction across all these dimensions. Despite these positive findings, the current evidence base lacks clarity in terms of how satisfaction is defined and measured. People living in rural and remote areas are generally satisfied with telehealth as a mode of service delivery as it may improve access to health care and avoid the inconvenience of travel.